Odnos prebivalcev zahodnega dela Šaleške doline do pokrajinskih virov - Špeh, Natalija (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Lignite minning was planned under the studied area in 1984. However it was rejected in 2002. The research project was founded in 1999) on the relation of the potentialy affected inhabitants to the landscape sources (especially the lignite). The results revealed almost uniform public opinion against the planned excavation, was expressed by both rural and urban population.
Keywords: naravni viri; pokrajinska ekologija; prebivalci; razvojna strategija; regionalni razvoj; Slovenia; Slovenija; sonaravni razvoj; Šalek Valley; Šaleška dolina